1978
DOI: 10.1073/pnas.75.12.6258
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dimorphism in influenza viruses: Characterization of stably associated hemagglutinin mutants differing in antigenicity and biological properties

Abstract: Influenza virus recombinant X-53 produced for use in the 1976 National Immunization Program for swine influenza was found to comprise two types of virions differing in their antigenic, replicative, and plaque-forming characteristics. One type, characteristic of X-53 and designated “L,” was relatively low-yielding in chicken embryos, produced small clear plaques in Madin-Darby dog kidney cells, and was selectively inhibited by heterotypic antibody to the A/sw/Cam/39 strain of swine influenza virus. The other, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
2

Year Published

1980
1980
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 16 publications
0
28
2
Order By: Relevance
“…Alternatively, the differences in antigenicity may be due to differences in the surface antigens themselves, and although all the vaccines carried HA and NA antigens derived from A/Victoria/75, differences in various phenotypic properties of the HA of influenza virus strains, indistinguishable by normal serological tests, have been reported (Kilbourne, 1978;Erickson & Kilbourne, 1980). Recent studies have shown that influenza A virus variants can readily emerge on passage (Brand & Palese, 1980), and such variants could differ in their antigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the differences in antigenicity may be due to differences in the surface antigens themselves, and although all the vaccines carried HA and NA antigens derived from A/Victoria/75, differences in various phenotypic properties of the HA of influenza virus strains, indistinguishable by normal serological tests, have been reported (Kilbourne, 1978;Erickson & Kilbourne, 1980). Recent studies have shown that influenza A virus variants can readily emerge on passage (Brand & Palese, 1980), and such variants could differ in their antigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenic mutants were repassaged at terminal dilution in the presence of a 1 in 2000 dilution of the monoclonal antibody and the virus harvests used to infect eggs to prepare a working stock of virus. Since passage of influenza A viruses in the absence of antibody pressure can lead on occasion to the selection of antigenic variants (Kilbourne, 1978), control virus clones were obtained from the parental A/Texas/77 virus using normal ascitic fluids and the Sero-epidemiological analysis using antigenic variants The six antigenic variants of A/Texas/77 described above were incorporated into the agarose of SRH plates to determine if they could be distinguished antigenically from the parental virus using human sera (Plate 1). All antigenic variants failed to react with a proportion of children's sera, although the same children's sera reacted with the parent A/Texas/77 virus.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly a mutant hemagglutinin gene has been fortuitously cloned during the construction of X47, or else a rare mutation in the population was selectively propagated under the conditions used to maintain and grow the X47 stock. An example of two allelic mutants in a recombinant stock and selective propagation of one type has been described by Kilbourne (1978). The exact difference between the hemagglutinin gene in the natural A/Victoria/3/75 and in X47 remains to be further characterized; for example, by probing with monoclonal antibodies.…”
Section: Characterization Of the Influenza Virus Strainmentioning
confidence: 99%